(untitled) (City: History, Culture, Society, 2023)
The problems of quality of life in the past are almost unexplored in Ukrainian history, and the concept itself is still only sporadically used in our historical science. At the same time, its use can provide productive research tools for understanding history through a person, his or her desires understanding history through a person, his or her desires, whims, needs, and habits. We approached researchers from different cities with a proposal to reflect on the extent to which quality of life is a relevant and interesting category for historical urbanism, and how "their" cities changed in the era of modernisation and, accordingly, how the life of the citizens (did not) change the lives of the citizens. While the list of questions remained unchanged, the respondents could choose those that better reflected those that better reflect their research interests or add their own observations.